Guidelines for Freshwater Pond Management in Bangladesh - Rashid, Ibrahim; Mithun, Mahmudul Hasan (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
The pond aquaculture sector in Bangladesh expands rapidly. Total fish production from pond aquaculture increasing day by day. Bangladesh ranks fifth in aquaculture production and becomes fourth in the tilapia production in the world. Total fish production in Bangladesh was about 4.27 million MT in 2017-18 fiscal years and the pond aquaculture production was about 1.9 million MT which contributes about 44.43% of the total fisheries production in 2017-18. That means pond aquaculture contributes a lot in Bangladesh fisheries sectors. For getting proper outcome from the pond aquaculture some basic guidelines should be followed during pre-stocking, stocking, and post stocking management of freshwater pond. Firstly, pond should be prepared properly before stocking of fish seed like aquatic weeds and predators should be eradicated with properly constructed the pond bottom and dike and then liming and fertilization should be done for making a better culture environment for fish. Good quality fish seed should be sock to the pond and feeding should be done properly. Periodic sampling for examining the proper growth and any disease infestation occurs should be done. Liming and fertilization should be done after stocking of fish seed if needed. Harvesting and marketing of fish should be done by considering some factors to get good profit.